Correlation of C-reactive proteins with chronic periodontitis - Shailja Chatterjee (Wolters Kluwer Medknow Publications, 2020)
Background: Acute-phase reactant proteins are synthesized in human body in response to chronic periodontal states. C-reactive protein (CRP) is a similar protein produced in response to chronic inflammatory conditions. Aim: The aim of the study was to correlate CRP levels in chronic periodontitis when compared to normal controls. Materials and Methods: A total of 45 individuals suffering from chronic periodontitis and an equal numbers of controls were included in the study. Blood samples were drawn from all individuals after obtaining informed consent, and CRP levels were estimated using an ELISA kit. Unpaired t-test was performed for statistical analysis. Results: The mean CRP levels were found to be higher in periodontitis individuals as compared to normal controls. However, no statistical significance was observed on comparing both the groups. Conclusion: An elevated CRP level was obtained in the diseased group, confirming the inflammatory background response to periodontal diseases.